The Growth Of Oil Palm (Elaeis guineensis Jacq.) In Pre Nursery With Planting Media Composition And Concentration Of Micro Fertilizer - I Wayan , Sugita; Yakup; Erizal , Sodikin; M. Umar , Harun (BIOVALENTIA: Biological Research Journal, 2025)
Planting media and micronutrients are important aspects of plant growth. Planting media rich in organic matter and micronutrients such as B and Cu are essential nutrients that must be fulfilled for oil palm plants (Elaeis guineensis Jacq). This study aims to determine the growth of oil palm in early nurseries with the composition of planting media and the concentration of microfertilizer application and determine the best treatment interaction for oil palm seedling growth. The research was conducted at UPT BPP Tungkal Jaya Kec. Musi Banyuasin from December 2023 to March 2024. The design used was a two-factor Randomized Block Design with three replications, each replication consisting of 48 plants so that there were 144 experimental units. The treatments consisted of (M0P0) 100% soil + 0 ml/plant vs (M1P1) 85% soil + 15% rice husk charcoal + 2 ml/plant vs (M2P2) 75% soil + 25% rice husk charcoal + 4 ml/plant and (M3P3) 50% soil + 50% rice husk charcoal + 6 ml/plant. The data obtained were analyzed using ANOVA, if there was a significant effect, it was continued with the Honest Real Difference test at the 5% level. The results showed that the composition of planting media had a significant effect on oil palm growth such as stem diameter, number of leaves, plant height, wet weight, dry weight and root length. However, microfertilizer concentration did not show a significant impact on growth. The interaction between growing media and microfertilizer affected certain variables such as leaf area, wet weight and root length.The conclusion of this research is that M3 planting media and P3 microfertilizer are effective in increasing the growth of oil palm seedlings. The use of organic planting media, loose and providing sufficient nutrients for plants found in the community environment